Undercurrents : From Oceanographer to University President - Byrne, John Vincent, 1928- (Book collections on Project MUSE., 2018)
"Undercurrents recounts the life and career of John Byrne, who started as a geologist at an oil company and retired as president of a major land grant university. He came to Oregon State in 1960 as a faculty member, later becoming department chair, dean, director of the Hatfield Marine Science Center, and vice president for Research and Graduate Studies. Along the way, he took leave from the university to serve the US government, first as a program director for oceanography at the National Science Foundation, and later as the administrator of the National Oceanic and Atmospheric Administration, before returning to OSU in 1984 as its twelfth president. Undercurrents demonstrates on every page the curiosity, intellect, and humanity that made John Byrne successful as a scientist, educator, and administrator."--